Congenital Cytomegalovirus Infection in High-Risk Canadian Infants: Report of a Pilot Screening Study. Issue 1 (2010) - Vaudry, Wendy; Rosychuk, Rhonda J; Lee, Bonita E; Cheung, Po Yin; Pang, XL; Preiksaitis, Jutta K
Abstract : OBJECTIVES: Congenital cytomegalovirus (cCMV) is the most common congenital infection; however, the epidemiology in Canada has not been recently examined. The present prospective study pilots tools for a population-based study of cCMV infection in Canada by determining the maternal seroprevalence and risk factors, the clinical characteristics and the incidence of cCMV using a variety of diagnostic tests in a cohort of high-risk infants in northern Alberta. METHODS: All infants born at the Royal Alexandra Hospital in Edmonton, Alberta, from June 1, 2003, to May 31, 2004, were screened for the study. Eligible infants were those with very low birth weights (VLBWs) or small for gestational age (SGA). Maternal CMV serostatus was determined, and chart review and parental interviews were completed. Neonatal urine and throat cultures, and polymerase chain reaction (PCR) were performed. Dried blood spots (DBS) were tested for CMV by PCR. RESULTS: In total, 213 infants were eligible for the study. Of these, 137 entered the study (79 VLBW and 58 SGA). Some families were not contacted for participation in the study due to neonatal deaths or early discharge. The mean age of the mothers was 27.6 years; 68% of the mothers were Caucasian and 16% were Aboriginal. The maternal CMV seroprevalence was 55%. Seropositivity was significantly associated with ethnicity (First Nations [100%]; Caucasian [34%]) and country of birth (outside Canada [94%]; Canadian born [45%]). The rate of cCMV was two in 137 (1.5%), with a rate of one in 79 (1.3%) for the VLBW infants and one in 58 (1.7%) for the SGA infants. Both had positive throat or urine specimens, but only the symptomatic infant was positive on DBS. CONCLUSIONS: A cCMV screening program should be universal and routine to successfully screen all newborns. Maternal CMV seropositivity varies widely within the Canadian population. In the present pilot study, DBS PCR was not a sensitive screening tool and throat swab was the best screening specimen.